Our Viewpoint about Therapeutic Tactics in Patients with Chronic Venous Insufficiency (Global Journal of Medical Research, 2022)
The research is based on a comparative analysis of the results after treatment of patients with chronic venous insufficiency (CVI) occurred in the lower extremities, patients were admitted to the hospital of the Tashkent Medical Academy and Akfa Medline hospital during the period 2016-2021. Patients were divided into 2 groups, which includes patients who treated with new treatment method and second group were control for comparison efficiency of the treatment. Conclusions were drawn about the shortcomings of the tactics of managing patients. During the treatment of patients of the main group, android programs were used to measure the area of trophic ulcers, an improved method of sanitation of trophic ulcers and a therapeutic algorithm for managing patients depending on the phase of the process, which led to an increase in the rate of ulcer granulation, and a reduction in the length of stay of patients in the hospital.
Keywords: varicose disease of the lower extremities; endovenous laser coagulation; radiofrequency ablation; sclerotherapy; vacuum therapy; trophic ulcer